2005
DOI: 10.1152/ajpheart.00851.2003
|View full text |Cite
|
Sign up to set email alerts
|

Increased superoxide production causes coronary endothelial dysfunction and depressed oxygen consumption in the failing heart

Abstract: This study examined whether increased superoxide (O2−·) production contributes to coronary endothelial dysfunction and decreased coronary blood flow (CBF) in congestive heart failure (CHF). To test this hypothesis, the effects of the low-molecular-weight SOD mimetic M40401 on CBF and myocardial oxygen consumption (MV̇o2) were examined in dogs during normal conditions and after CHF was produced by 4 wk of rapid ventricular pacing. The development of CHF was associated with decreases of left ventricular (LV) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…Thus, CHF is associated with decreased EC-SOD protein content or activity [9][10][11] and overexpression of EC-SOD has been reported to protect the heart against ischemia-reperfusion injury [25,26] (an effect not enhanced by administration of catalase, demonstrating that protection was dependent upon removal of superoxide but not hydrogen peroxide). In contrast to these previous reports in failing hearts, in the present study EC-SOD protein was significantly increased in the periinfarct region, and SOD1 protein was increased in both the peri-infarct and remote regions of the infarcted hearts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CHF is associated with decreased EC-SOD protein content or activity [9][10][11] and overexpression of EC-SOD has been reported to protect the heart against ischemia-reperfusion injury [25,26] (an effect not enhanced by administration of catalase, demonstrating that protection was dependent upon removal of superoxide but not hydrogen peroxide). In contrast to these previous reports in failing hearts, in the present study EC-SOD protein was significantly increased in the periinfarct region, and SOD1 protein was increased in both the peri-infarct and remote regions of the infarcted hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in whom EC-SOD binding to endothelial cells is decreased as the result of substitution of arginine-213 by glycine (R213G) have an increased incidence of hypertension [7] and increased risk of ischemic heart disease [7,8], implying that impaired EC-SOD binding or decreased myocardial EC-SOD content can increase the vulnerability to cardiovascular disease. Several recent studies have demonstrated that EC-SOD expression is decreased in the failing heart, and this was associated with evidence of increased myocardial oxidative stress and endothelial dysfunction [9][10][11]. However, whether EC-SOD can influence ventricular oxidative stress and remodeling after MI remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…129 Administration of a low-molecular-weight superoxide dismutase mimetic to dogs protects against pacing-induced heart failure and preserves coronary endothelial function. 130 Antioxidants (eg, vitamin C) seem to improve endothelial functionality and reduce the inflammatory response in patients with heart failure. 127 As mentioned, endogenous NO may regulate myocardial mitochondrial oxidative phosphorylation by directly competing with oxygen at complex IV (see above, under section Endothelial NO Production).…”
Section: Involvement Of Endothelial Mitochondria In Heart Failurementioning
confidence: 99%
“…In vitro studies have shown that iNOS not only produces NO but is also capable of generating superoxide independently of NO (39). Moreover, not only is superoxide itself toxic to the heart, but it also leads to the formation of H 2 O 2 , which may also be toxic (5,16,24,29). Thus blockade or deletion of iNOS may decrease not only NO production but also formation of superoxide, in turn reducing generation of H 2 O 2 .…”
Section: Induction Of Inos and Oxidative Stressmentioning
confidence: 99%